A Low-Cost Multispectral Imaging System for Microscale Applications - Penman, Daneel (Wellington Faculty of Engineering Symposium, 2023)
Multispectral imaging (MSI) is an imaging technology that captures spectral data across multiple individual wavelengths not typically visible under normal light. This has several applications, from astronomy to forensics, but is not widely available due to expensive instrumentation. To address this, a low-cost multispectral imaging device for application in micro-scale imaging was developed. This system uses an array of light emitting diodes (LEDs) on a flexible printed circuit board (PCB) to create a diverse set of wavelengths to illuminate the sample. These PCBs are mounted in an acrylic housing designed to allow illumination in transmission and reflection format. The system is controlled through an ESP-32-S3 microcontroller and some peripheral electronics. A monochrome machine vision camera, controlled by Pylon viewer software is used for image acquisition. Multivariate data analysis of the images was done using various freely available software packages. The system was tested on a series of dried milk fluid drops to discern their composition as proof of the viability of the system.